Kedudukan Kantor Urusan Agama Dalam Pernikahan Warga Muslim di Indonesia - Eka Astuti; Heni Maryani; Noviar Sutatno; Ahmad Zaenuri; Siti Budiasih; Muhammad Jafit Iqbal; Setya Sunarsih; Zainul Arifin (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
The study aims to describe the duties and authorities of the Religious Affairs Office (KUA) of Tegalrejo sub-district/district in the field of marriage, divorce, and reconciliation (rujuk) for the Muslim community so that its position in the implementation of Islamic family law in Indonesia can be analyzed. Through sociological juridical research with data collection from observation, interviews and documentation and descriptive analysis, it was found that the KUA is an extension of the government in implementing Islamic family law in the sub-district/district while also implementing the provisions and decisions of the Religious Court in accordance with PMA No. 34 of 2016. Therefore, the proactive nature in expanding and deepening the understanding of Islamic family law to the community is that the KUA is not limited to registering marriages, but functions from the beginning of marriage to the formation of a sakinah family that is a lifelong process.